Molecular Marker-Assisted Selection of Rice Grain Quality on Rice (Oryza sativa L.) Lines Tolerant to Fe Toxicity Stress - Utami, Silvia; Widyastuti, Utut; Utami, Dwinita Wikan; Rosdianti, Ida; Lestari, Puji (Journal of Tropical Life Science, 2017)
The elite rice has been produced, including iron (Fe) tolerant varieties. To get the appropriate rice lines which superior not only Fe tolerant but also have good grain quality needs to be developed selection system, especially in the use of molecular markers. This study was aimed to develop molecular markers for selection the rice grain quality characters of selected rice lines Fe tolerant. A total of 30 selected Fe tolerant rice lines and 5 parents as control lines were used in this research. Characterization of grain quality were quantitatively using the standard. While for genotyping analysis used 19 molecular markers of STS, SSR, Indel and SNP. This study showed that 14 of 19 markers result polymorphic DNA band (DNA markers). Association analysis of genotype and phenotype showed that 10 of 14 markers were significantly (p < 0.05) related to high quality of rice grain. Among four types of markers used in this study, STS was the most widely associated significantly with four characters of rice quality. The phenotyping analysis showed that the physical grain and palatability quality which obtained from the total mean of 30 rice lines tested tend to nearly with the parentâ€™s value as controls lines. The most of these lines were included in the group IV of National Rice Grain Quality Standard (SNI). The amylose content (AC) showed that the texture was varied from firm and dry (high AC) to soft and sticky (low AC). The association results showed that there were significant (p â‰¤ 0.05) markers related with the biosynthesis starch genes, i.e: SBE1, SS1, SSIIa, GPA, PUL and S3cl which contributed on the character of rice palatability. These selected significant markers could be useful for screening of other population with Fe tolerant and/ or other desired morpho-agronomical traits in support of rice breeding program in Indonesia.